Profiles of Burnout and Response to the COVID-19 Pandemic Among General Surgery Residents at a Large Academic Training Program. (April 2023) - Nguyen, May-Anh; Castelo, Matthew; Greene, Brittany; Lu, Justin; Brar, Savtaj; Reel, Emma; Cil, Tulin D.
Background: COVID-19 has placed demands on General Surgery residents, who are already at high risk of burnout. This study examined the pandemic's impact on burnout and wellness among General Surgery residents at a large training program. Methods: General Surgery residents at our institution completed a survey focused on self-reported burnout, mental health, perceptions of wellness resources, and changes in activities during the pandemic. Burnout was measured using the Maslach Burnout Inventory (MBI). Unsupervised machine learning ( k-means clustering) was used to identify profiles of burnout and comparisons between profiles were made. Results: Of 82 eligible residents, 51 completed the survey (62% response rate). During COVID-19, 63% of residents had self-described burnout, 43% had depression, 18% acknowledged binge drinking/drug use, and 8% had anxiety. There were no significant differences from pre-pandemic levels ( p all >.05). Few residents perceived available wellness resources as effective (6%). Based on MBI scores, the clustering analysis identified three clusters, characterized as "overextended", "engaged", and "ineffective". Engaged residents had the least concerning MBI scores and were significantly more likely to exercise, retain social contact during the pandemic, and had less self-reported anxiety or depression. Research residents were overrepresented in the ineffective cluster (46%), which had high rates of self-reported burnout (77%) and was characterized by the lowest personal accomplishment scores. Rates of self-reported burnout for overextended and engaged residents were 73% and 48%, respectively. Conclusion: Surgical residents have high rates of self-reported burnout and depression during the COVID-19 pandemic. Clusters of burnout may offer targets for individualized intervention.